Tourism and Water Pollution - The River Pamba - Lata Marina Varghese
The River Pamba is the main source of drinking water to the people of Central Travancore in Kerala, the scenic and exotic southern state of India. It is considered as a ‘holy’ river due to the presence of Sabarimala Lord Ayyappa’s Temple on its banks. River Pamba is now in a state of high contamination and pollution mainly due to the impact of unrestricted tourism activities. The present state of degradation of the river is due to anthropogenic activities such as directing human waste and dumping of solid waste from hotels and other establishments into it causing water pollution and giving rise to water-borne diseases. The impact of anthropogenic pressure on the river is quite high and hence drastic steps and continuous monitoring is essential.